Asymptomatic man with an incidental finding of a massive empyema. Issue 9 (10th September 2020) - Gupta, Kashvi; Stuewe, Elena; Barry, Marianne
Abstract : We describe the case of a 67-year-old asymptomatic man who was referred to our hospital for abnormal laboratory results. He was incidentally found to have a massive empyema without underlying bronchopulmonary pneumonia. Following thoracentesis, he was diagnosed with chronic Streptococcus anginosus empyema. Therapeutic thoracentesis and treatment with tissue plasminogen activator and deoxyribonuclease failed to resolve the empyema, and there was residual loculated pleural fluid that was surrounded by a thick rind. The patient was referred to thoracic surgery for decortication of the pleural space via video-assisted thoracoscopic surgery. At 2-month follow-up, the patient had complete re-expansion of the lung tissue.